2023
DOI: 10.3390/nano13040703
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Violet-Assisted Scalable Method to Fabricate Oxygen-Vacancy-Rich Titanium-Dioxide Semiconductor Film for Water Decontamination under Natural Sunlight Irradiation

Abstract: This work reports the fabrication of titanium dioxide (TiO2) nanoparticle (NPs) films using a scalable drop-casting method followed by ultra-violet (UV) irradiation for creating defective oxygen vacancies on the surface of a fabricated TiO2 semiconductor film using an UV lamp with a wavelength oof 255 nm for 3 h. The success of the use of the proposed scalable strategy to fabricate oxygen-vacancy-rich TiO2 films was assessed through UV–Vis spectroscopy, X-ray photoelectron spectroscopy (XPS), X-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The induced OVs promoted the photodegradation efficiency of the Z-scheme mechanism (between TiO 2 nanorods/g-C 3 N 4 nanosheets) toward phenol under visible light illumination. 225 Oxygen vacancy-mediated sandwich-structured TiO 2−x /ultrathin g-C 3 N 4 /TiO 2-x showed a direct Z-scheme photocatalytic mechanism with an excellent TC photodegradation efficiency (87.7% for 90 min) employing • O 2 − , h + and • OH reactive species (by Ni et al). This excellent activity is related to the special 3D structure, the Z-scheme heterojunction expediting charge transfer, and enhanced active species formation.…”
Section: Oxygen Vacancy (Ov)mentioning
confidence: 99%
See 1 more Smart Citation
“…The induced OVs promoted the photodegradation efficiency of the Z-scheme mechanism (between TiO 2 nanorods/g-C 3 N 4 nanosheets) toward phenol under visible light illumination. 225 Oxygen vacancy-mediated sandwich-structured TiO 2−x /ultrathin g-C 3 N 4 /TiO 2-x showed a direct Z-scheme photocatalytic mechanism with an excellent TC photodegradation efficiency (87.7% for 90 min) employing • O 2 − , h + and • OH reactive species (by Ni et al). This excellent activity is related to the special 3D structure, the Z-scheme heterojunction expediting charge transfer, and enhanced active species formation.…”
Section: Oxygen Vacancy (Ov)mentioning
confidence: 99%
“…Similarly, the TiO 2– x /g-C 3 N 4 nanorod array photoelectrode was fabricated by Qi et al via urea drop calcination and NaBH 4 reduction. The induced OVs promoted the photodegradation efficiency of the Z-scheme mechanism (between TiO 2 nanorods/g-C 3 N 4 nanosheets) toward phenol under visible light illumination …”
Section: Photodegradation On Anion Vacanciesmentioning
confidence: 99%
“…Among these, microscope techniques, such as atomic-resolution spherical aberration-corrected transmission electron microscopy, scanning transmission electron microscopy (STEM), and scanning tunneling microscopy, are employed to verify the presence of vacancies [ 33 ]. Spectroscopy techniques, on the other hand, encompass electron spin resonance (ESR) spectroscopy, X-ray photoelectron spectroscopy (XPS), X-ray absorption fine structure (XAFS), in situ electron energy loss spectroscopy, transient absorption, Raman spectroscopy, thermogravimetric, time-resolved absorption, and fluorescence spectroscopy [ 34 , 35 ]. For instance, STEM, with the aid of probe-forming aberration correctors, can distinguish between surface and bulk vacancies, offering insights into local atomic structure and chemical composition at the atomic level.…”
Section: Characterization and Engineering Strategies Of Sulfur Vacanciesmentioning
confidence: 99%
“…Under visible light irradiation, the as-synthesized heterojunctions significantly enhanced the photodegradation activity of rhodamine B, thereby providing the possibility of the removal of photocatalytic pollutants using solar light [ 2 ]. In another study, Alyami reported an ultra-violet-assisted scalable method to construct TiO 2 photocatalysts with abundant oxygen vacancies for photocatalytic dye removal [ 3 ]. The defective TiO 2 with Ti 3+ exhibited stronger visible light absorption and much higher removal efficiency of methylene blue under visible light illumination than pristine TiO 2 [ 3 ].…”
mentioning
confidence: 99%
“…In another study, Alyami reported an ultra-violet-assisted scalable method to construct TiO 2 photocatalysts with abundant oxygen vacancies for photocatalytic dye removal [ 3 ]. The defective TiO 2 with Ti 3+ exhibited stronger visible light absorption and much higher removal efficiency of methylene blue under visible light illumination than pristine TiO 2 [ 3 ]. Similarly, Wang et al developed B-doped g-C 3 N 4 /black TiO 2 Z-Scheme heterojunctions with enhanced charge separation efficiency and increased tetracycline sorption ability [ 4 ].…”
mentioning
confidence: 99%